Panggilan Orang Percaya dalam Berapologetika - Mukti, Guntur Hari (Kharisma: Jurnal Ilmiah Teologi, 2020)
The calling of faith as a believer has a lot of emphasis on being a witness for many people, so that through life's testimony many people become attracted to and believe in the Savior of the Lord Jesus Christ. The calling of apologetics in the life of faith is forgotten and as if it is only a part of those who get the title "Servant of God". The calling of Believers in Apologetics is a general calling as well as a call to be witnesses for Christ, because many around us are people who hold us accountable for the Christian faith, therefore through this writing all believers can be made aware that apologetics is a calling that is glorious in the life of the believer. This research is structured using descriptive qualitative methods through literature study and conclusions are generally drawn based on deductive methods to generate understanding as a believer in his calling to defend the faith.Panggilan hidup beriman sebagai orang percaya banyak bertitik tumpu pada menjadi saksi bagi banyak orang, sehingga melalui kesaksian hidup banyak orang menjadi tertarik dan percaya kepada Tuhan Yesus Kristus Juru Selamat. Panggilan berapologetika dalam hidup beriman terlupakan dan seolah itu hanya menjadi bagian dari mereka yang mendapat gelar “Hamba Tuhan”. Panggilan Orang Percaya dalam Berapologetika adalah panggilan yang umum sebagaimana panggilan untuk menjadi saksi bagi Kristus, sebab banyak disekitar kita orang yang meminta pertanggunganjawaban iman Kristen yang kita percaya, oleh sebab itu melalui tulisan ini semua orang percaya kiranya bisa disadarkan bahwa berapologetika itu adalah suatu panggilan yang mulia dalam hidup orang percaya. Penelitian ini disusun menggunakan metode kualitatif deskriptif melalui studi Literatur dan kesimpulan secara umum diambil berdasarkan metode deduktif untuk melahirkan pemahaman sebagai orang percaya dalam panggilannya untuk membela iman.